Workforce Agility through Psychological Empowerment and Organizational Learning that Supports the Role of Logistics Company Supervisors and Forwarders (Journal of Namibian Studies : History Politics Culture, 2023)
Agile employees are resources who are able to handle unexpected and adaptive things in dynamically changing in an uncertain business environment and are proactively able to analyze problems and find solutions, interactive and able to read opportunities at the right time and conditions in a creative way , effective, and efficient. This study aims to examine the effect of psychological empowerment and organizational learning on workforce agility, and to examine the effect of psychological empowerment through organizational learning on workforce agility. The study, which took 68 employees at the supervisor level from four logistics companies and forwarders in an industrial area in Surabaya, distributed an instrument in the form of a Likert scale for data collection. The results of the analysis of hypothesis testing through path analysis shows psychological empowerment has a positive effect on workforce agility in supervisors in logistics and forwarder companies. The value of the coefficient of determination shows that psychological empowerment is able to contribute to the workforce agility of the supervisors. organizational learning has a positive effect on workforce agility in supervisors. psychological empowerment through organizational learning has an effect on workforce agility in supervisors in logistics and forwarder companies. Further research contribution are required on work agility.